New Information about Albert Einstein's brain - Falk, Dean (Frontiers in Evolutionary Neuroscience, 2009)
In order to glean information about hominin (or other) brains that no longer exist, details of external neuroanatomy that are reproduced on endocranial casts (endocasts) from fossilized braincases may be described and interpreted. Despite being, of necessity, speculative, such studies can be very informative when conducted in light of the literature on comparative neuroanatomy, paleontology, and functional imaging studies. Albert Einstein's brain no longer exists in an intact state, but there are photographs of it in various views. Applying techniques developed from paleoanthropology, previously unrecognized details of external neuroanatomy are identified on these photographs. This information should be of interest to paleoneurologists, comparative neuroanatomists, historians of science, and cognitive neuroscientists. The new identifications of cortical features should also be archived for future scholars who will have access to additional information from improved functional imaging technology. Meanwhile, to the extent possible, Einstein's cerebral cortex is investigated in light of available data about variation in human sulcal patterns. Although much of his cortical surface was unremarkable, regions in and near Einstein's primary somatosensory and motor cortices were unusual. It is possible that these atypical aspects of Einstein's cerebral cortex were related to the difficulty with which he acquired language, his preference for thinking in sensory impressions including visual images rather than words, and his early training on the violin.